Atypical Optic Neuritis in an Immunocompetent Patient with Orbital - Masnon, Nurul ’Ain; Wan Hitam, Wan Hazabbah; Thavaratnam, Lakana Kumar; Abd Munaaim, Maimunah (IIUM Medical Journal Malaysia, 2021)
Aspergillosis infection in immunocompetent individuals is an uncommon entity. Non-specific presentation could delay in the diagnosis and management. We describe a case of orbital aspergillosis with cavernous sinus extension in a healthy lady. A 67-year-old lady presented with left eye decreased vision, preceded by non-specific headache for three weeks. Visual acuity deteriorated followed by ptosis and left ocular restrictions after corticosteroids therapy. Examination revealed poor left eye visual acuity with ptosis, anisocoria and total ophthalmoplegia. MRI orbit and brain demonstrated a heterogenous left orbital apex lesion extending to cavernous sinus. Transsphenoidal endoscopic biopsy revealed Aspergillus infection at the left retro-orbital space and the sphenoid sinus. Patient was treated with long duration of oral voriconazole. Ptosis and ophthalmoplegia resolved but left optic atrophy remained. In conclusion, orbital aspergillosis may carry a poor visual prognosis and intracranial spread does easily occur. Early treatment may lead to a better outcome in immunocompetent patients.